FAKTOR-FAKTOR YANG MEMPENGARUHI PENERAPAN SISTEM AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (SAKIP) PADA PEMERINTAH PROVINSI SULAWESI UTARA - Tahir, Harsya K.; Poputra, Agus T.; Warongan, Jessy D. L. (Universitas Sam Ratulangi, 2016)
The purpose of this research is to analysis the factors which affecting the implementation of the SAKIP in Government of North Sulawesi, the contain is factor awareness on the laws and regulation (X1), factor organizationalÂ commitment (X2) and factor role of APIP (X3) toward implementation of SAKIP (Y). Method that use in this research are quantitative method. The data analysis technique has been done by using the multiple linear regressions analysis. Result of the research according the partial test show that awareness on the laws and regulation no significantly effect to the implementation of SAKIP, whereas the organizatoinal commitment and role of APIP has significantly effect to the implementation of SAKIP. The value from coefficient of determination test amount of 43,7% has been effect by awareness on the laws and regulation, organizatoinal commitment, role of APIP, whereas the remaining 56,3% is influenced by other factors outside this research. KeywordsÂ : awareness of the laws and regulation, commitment of organization, role of APIP, and SAKIP